2021
DOI: 10.1021/acs.joc.1c00592
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Acceptorless Dehydrogenative Coupling–Decyanation under Nickel Catalysis

Abstract: The development of new catalytic processes based on abundantly available starting materials by cheap metals is always a fascinating task and marks an important transition in the chemical industry. Herein, a nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles followed by decyanation of nitriles to access diversely substituted olefins is reported. This unprecedented CC bond-forming methodology takes place in a tandem manner with the formation of formamide as a sole byproduct. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…Synthesis of α,β-unsaturated ketone using alcohol α,β-Unsaturated ketones have broad applications in the synthesis of pharmaceuticals, biologically active compounds, Scheme 19 Ni-NNN complex catalyzed decyanative olefination of nitriles using alcohol. 46 Scheme 20 Plausible catalytic cycle for Ni-NNN complex catalyzed decyanative olefination of nitriles using alcohol.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of α,β-unsaturated ketone using alcohol α,β-Unsaturated ketones have broad applications in the synthesis of pharmaceuticals, biologically active compounds, Scheme 19 Ni-NNN complex catalyzed decyanative olefination of nitriles using alcohol. 46 Scheme 20 Plausible catalytic cycle for Ni-NNN complex catalyzed decyanative olefination of nitriles using alcohol.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 99%
“…In 2021, Balaraman and co-workers disclosed an unprecedented olefin ( E ) synthesis using nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles via a decyanation pathway, 46 where previous reports had shown α-alkylated/alkenylated products with the same starting materials. After screening several reaction conditions, the optimization experiments revealed that 4-methoxybenzyl alcohol and 2-phenylacetonitrile underwent a Ni-catalyzed (Cat.…”
Section: Transition Metal-catalyzed α-Olefination Of Nitrilesmentioning
confidence: 99%
“…The olefination of alcohols using Wittig alkenylation, sulfones or via dehydrogenative decyanation reaction of cyanide was also performed by various groups for the regioselective synthesis of olefinated products 158-160 (Scheme 67). [126][127][128] An attempt for the synthesis of resveratrol (3,5,4 0 -trihydroxy-trans-stilbene), 129 was also successful. Resveratrol is a phytoalexin that inhibits the growth of bacteria and fungus.…”
Section: Alkenylation Of Ylides Sulfones and Cyanidesmentioning
confidence: 99%
“…The unprecedented report of a nickel catalyzed dehydrogenative–decynative coupling of alcohols with nitriles to establish E-olefins was published recently by Balaraman's research group (Scheme 41a). 52 Various primary and secondary alcohols were employed in combination with benzylcyanide derivatives under optimized reaction conditions. Electron withdrawing groups decreased the yield of the reaction.…”
Section: C-alkylationmentioning
confidence: 99%